In vitro digestibility of mountain‐grown irrigated perennial legume, grass and forb forages is influenced by elevated non‐fibrous carbohydrates and plant secondary compounds. (3rd August 2020) - Zhang, Yunhua; MacAdam, Jennifer W; Villalba, Juan J; Dai, Xin
Abstract: BACKGROUND: Perennial legumes cultivated under irrigation in the Mountain West USA have non‐fibrous carbohydrate (NFC) concentrations exceeding 400 g kg −1, a level commonly found in concentrate‐based ruminant diets. Our objective was to determine the influence of NFC concentration and plant secondary compounds on in vitro rumen digestion of grass, legume and forb forages compared with digestion of their isolated neutral detergent fiber (NDF) fraction. Forages were composited from ungrazed paddocks of rotationally stocked, irrigated monoculture pastures between May and August 2016, frozen in the field, freeze‐dried, and ground. RESULTS: The maximum rate (RMax ) of gas production was greater for the legumes alfalfa (ALF; Medicago sativa L.) and birdsfoot trefoil (BFT; Lotus corniculatus L.) than for the legume cicer milkvetch (CMV; Astragalus cicer L.) the grass meadow brome (MBG; Bromus riparius Rehm.) and the non‐legume forb small burnet (SMB; Sanguisorba minor Scop.), and intermediate for the legume sainfoin (SNF; Onobrychis viciifolia Scop.). The RMax of isolated NDF was greatest for BFT and CMV, intermediate for ALF, SNF and SMB and least for MBG. CONCLUSIONS: More than 900 g of organic matter kg −1 dry matter of legumes was digested after 96 h. Across forages, the extent of whole‐plant digestion increased with NFC and crude protein concentrations, decreased with NDF concentrations, and was modulated by secondary compounds. The extent of digestion of isolated NDF decreased with concentration of lignin and residual tannins. © 2020 Society of Chemical Industry